Dispositional Optimism and Context Sensitivity: Psychological Contributors to Frailty Status Among Elderly Outpatients - Sardella, Alberto; Lenzo, Vittorio; Bonanno, George A.; Martino, Gabriella; Basile, Giorgio; Quattropani, Maria C. (Frontiers in Psychology, 2021)
The association of resilience-related factors with frailty is a recent research topic. Dispositional optimism and context sensitivity are two psychological factors that differently contribute to individual resilience. This study aimed at investigating whether dispositional optimism and context sensitivity might contribute to a multifactorial model of frailty, together with established relevant factors such as cognitive and physical factors. This cross-sectional study involved 141 elderly outpatients (42 male, 99 female) aged ≥ 65 years, who were referred to the Geriatrics and Multidimensional Evaluation Clinic of the University Hospital of Messina. We used the following measures: the Mini-Mental State Examination (MMSE) to screen for global cognitive functioning; 4-meter gait speed and handgrip strength to measure physical performance; a 35-item Frailty Index (FI) to evaluate patients’ frailty status; the revised Life Orientation Test (LOT R) to gauge dispositional optimism; and the Context Sensitivity Index (CSI) to measure context sensitivity. We found that LOT R (β = 0.190, p = 0.038), CSI (β = ‑0.191, p = 0.035), and MMSE (β = 0.466, p < 0.001) were all significantly associated with FI. Gait speed was only marginally associated with FI (β = 0.184, p = 0.053). The present study showed a novel association of dispositional optimism and context sensitivity with frailty among elderly outpatients. These preliminary findings support a multidimensional approach to frailty in which even peculiar psychological features might provide a significant contribution.